Susceptibility to cyflumetofen in populations of the citrus leprosis mite, Brevipalpus yothersi, from Brazilian citrus orchards - Escobar‐Garcia, Hector Alonso [UNESP]; de Andrade, Daniel Júnior [UNESP] (Wiley, 2025)
BACKGROUND: Brevipalpus yothersi Baker (Acari: Tenuipalpidae), the citrus leprosis mite, is currently the most economically significant mite pest in commercial citrus orchards, serving as the vector of citrus leprosis virus C (CiLV-C, Cilevirus leprosis). Its control has traditionally relied on the intensive use of synthetic acaricides, raising concerns regarding field efficacy and resistance development. To support integrated pest management (IPM) and resistance management strategies, monitoring the susceptibility of field populations is essential. Cyflumetofen, an acaricide that inhibits mitochondrial complex II electron transport, offers a distinct mode-of-action (MoA) for mite control. This study aimed to characterize the susceptibility of B. yothersi populations to cyflumetofen to evaluate its potential use in sustainable resistance management and prolong its efficacy in commercial applications. RESULTS: Field populations exhibited high susceptibility to cyflumetofen, with median lethal concentration (LC50LC₅₀) values ranging from 0.36 to 1.31 mg L-1 and 95% lethality (LC95) values from 1.22 to 4.99 mg L-1. Resistance levels were low, with resistance ratios below 2.79-fold at LC50 and below 3.06-fold at LC95, relative to a susceptible reference population. CONCLUSION: Cyflumetofen proved effective against B. yothersi in the surveyed regions, with field populations showing high susceptibility. To maintain its efficacy and extend its commercial longevity, rotation with other synthetic acaricides featuring different MoAs is recommended as part of a resistance management plan. © 2025 The Author(s). Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.